On pairwise weakly Lindelof bitopological spaces - Kilicman, Adem; Salleh, Zabidin (Iranian Mathematical Society, 2013)
In the present paper we introduce and study the notion of pairwise weakly Lindelof bitopological spaces and obtain some results. Further, we also study the pairwise weakly Lindelof subspaces and subsets, and investigate some of their properties. It is proved that a pairwise weakly Lindelöf property is not a hereditary property.